2013
DOI: 10.1371/journal.pone.0084225
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of SHOX2 and SEPT9 DNA Methylation and Cytology in Benign, Paramalignant and Malignant Pleural Effusions

Abstract: Pleural effusions (PE) are a common clinical problem. The discrimination between benign (BPE), malignant (MPE) and paramalignant (PPE) pleural effusions is highly important to ensure appropriate patient treatment. Today, cytology is the gold standard for diagnosing malignant pleural effusions. However, its sensitivity is limited due to the sometimes low abundance of tumor cells and the challenging assessment of cell morphology in cytological samples. This study aimed to develop and validate a diagnostic test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…This semiquantitative result is then transformed into a qualitative result (testpositive and test-negative). However, an advantage of DNA methylation testing is the simplicity and high accuracy, robustness and repeatability of a quantitative analysis using a calibrator and an adapted ΔΔCT method [49,50]. Reporting the quantitative test result therefore might help to improve the test performance in the future.…”
Section: Analyticsmentioning
confidence: 99%
“…This semiquantitative result is then transformed into a qualitative result (testpositive and test-negative). However, an advantage of DNA methylation testing is the simplicity and high accuracy, robustness and repeatability of a quantitative analysis using a calibrator and an adapted ΔΔCT method [49,50]. Reporting the quantitative test result therefore might help to improve the test performance in the future.…”
Section: Analyticsmentioning
confidence: 99%
“…This product has been used clinically in combination with the Applied Biosystems 7500 Fast or Fast DX Real-Time polymerase chain reaction (PCR) System. Although the assay has been performed clinically with bronchoalveolar lavage fluid samples collected at bronchoscopy [13][14][15], its applications with other types of samples are also under investigation, and these include lung cancer tissue [17], lymph node tissue around lung cancer [19], pleural effusion (hydrothorax) [20,21], and plasma [16]. These studies showed that histology or cytology samples obtained for pathological or cytological examinations can also be used for the SHOX2 gene methylation assay to confirm suspected diagnosis.…”
Section: Samples Used For Shox2 Gene Methylation Assaymentioning
confidence: 99%
“…However, a large discrepancy has been observed in sensitivity between samples. The sensitivity for lung tissue/lymph nodes samples, bronchial lavage samples and plasma samples was above 94 % [17,19], between 64-78 % [13][14][15] and about 60 % [16], respectively, and the positivity rate with pleural effusion samples was less than 40 % [20,21]. Therefore, it shows a clear trend in sensitivity: lung cancer tissue & lymph node tissue [ bronchoalveolar lavage fluid [ plasma.…”
Section: Sensitivity and Specificity Of Shox2 Gene Methylation Assaymentioning
confidence: 99%
See 2 more Smart Citations